17β-Estradiol Induced Effects on Anterior Cruciate Ligament Laxness and Neuromuscular Activation Patterns in Female Runners - Khowailed, Iman Akef; Petrofsky, Jerrold; Lohman, Everett; Daher, Noha; Mohamed, Olfat (Journal of women's health (Larchmont, N.Y. 2002), 2015)
We investigate the effects of 17β-Estradiol across phases of menstrual cycle on the laxness of the anterior cruciate ligament (ACL) and the neuromuscular control patterns around the knee joint in female runners. Twelve healthy female runners who reported normal menstrual cycles for the previous 6 months were tested twice across one complete menstrual cycle for serum levels of 17β-estradiol, and knee joint laxity (KJL). Electromyographic (EMG) activity of the quadriceps and hamstrings muscles was also recorded during running on a treadmill. The changes in the EMG activity, KJL, and hormonal concentrations were recorded for each subject during the follicular and the ovulatory phases across the menstrual cycle. An observed increase in KJL in response to peak estradiol during the ovulatory phase was associated with increased preactivity of the hamstring muscle before foot impact (p<0.001). A consistent pattern was also observed in the firing of the quadriceps muscle recruitment pattern throughout the follicular phase associated with decreased hamstring recruitment pattern during weight acceptance phase of running (p=0.02). Additionally, a low ratio of medial to lateral quadriceps recruitment was associated with a significant reduction of the quadriceps to hamstring co-contraction ratio during the follicular phase. Changes in KJL during the menstrual cycle in response to 17β-estradiol fluctuations changes the neuromuscular control around the knee during running. Female runners utilize different neuromuscular control strategies during different phases of the menstrual cycle, which may contribute to increased ACL injury risk.